Evaluasi Pelaksanaan Sosialisasi Program Jaminan Kesehatan Nasional dari Aspek Struktur dan Interaksi Sosialisasi Pada Bulan Januari-Maret 2014 di Puskesmas Ngesrep Semarang - Azaria Yenni Amira (Jurnal Kesehatan Masyarakat (Undip), 2015)
Abstrack : Implementation of programs organized by the BPJS JKN in Indonesia involving also public health as basic level health care givers. Which came into effect January 1, 2014. Since the enactment of the program many of the problems occurred JKN at Clinics that have cooperated with the difference between the reference location BPJS, changes in the number of patients received the drug and others. Based on these problems required an evaluation of the program socialization has been done by JKN BPJS Health Clinics Ngesrep Semarang. This research uses qualitative descriptive approach. The number of key informants as many as 5 people consisting of head of primary health services Management Unit and primary health care staff in the management of health and triangulation are 4 people consisting of doctors, nurses, administration and finance section as well as the Pharmacy Clinics Ngesrep Semarang. The results showed that with the material, the tools used and the methods used when socializing activities of socialization has been going well. There are a few things that need to be done by the BPJS, among other Health improvements of the rule concerning the technical implementation of the program and the system in the hope of JKN does not happen error in health care personnel when dealing with patients. It is recommended that BPJS can provide socialization to society, provide training to health workers as well as rules on patenting programs soon JKN.